Pyrimidyl isophthalate metal organic frameworks for gas storage - Benson, Oguarabau (2016)
This thesis focuses on the syntheses and gas sorption studies of a series of novel metal-organic frameworks constructed from Cu(II) paddlewheels and pyrimidyl isophthalate ligands. The effects of ligand extension and functionalisation on the framework structures and properties are investigated and discussed under respective chapters. Chapter 1 introduces metal-organic frameworks (MOFs), places the thesis in its scientific context, and discusses the syntheses of the ligands and MOFs with emphasis on the design of pyrimidyl isophthalate MOFs as having no open metal sites. Chapter 2 describes the syntheses of two porous phenyl-based pyrimidyl isophthalate frameworks to investigate the effect of extending linker length on the MOF structure, surface area and gas uptake capacities. Chapter 3 discusses the concept of pore functionalisation of the pyrimidyl isophthalate MOFs with amide pendant groups. Chapter 4 centres on the incorporation of alkyne groups in the ligand design and the impact on the pore characteristics and gas uptake properties. Chapter 5 is an overview of the experimental results and includes comparisons of the different ligands, the crystal structures of the MOFs and their gas uptake capabilities. The conclusions for the thesis and resulting future research perspectives are stated in Chapter 6.